2009
DOI: 10.1590/s0074-02762009000400013
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet has a prominent effect upon the course of chronic schistosomiasis mansoni in mice

Abstract: This study investigated whether a long-term high-fat diet has an effect on the outcome of chronic murine schistosomiasis mansoni compared to a standard diet. Swiss Webster female mice (3 weeks old) were fed each diet for up to six months and were then infected with 50 Schistosoma mansoni cercariae. Their nutritional status was assessed by monitoring total serum cholesterol and body mass. Infected mice were examined 6-17 weeks post infection to estimate the number of eggs in faeces. Mice were euthanised the nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…It is proposed that glycolysis provides energy sufficient for the survival of schistosomes, while vitellocytes are highly dependent on oxidative phosphorylation of lipids [22]. Schistosomes infecting mice living on high-fat diets have a higher fecundity rate than worms infecting mice living with a regular diet [23]. Vitellogenesis was also enriched in the blue module.…”
Section: Expression Of Genes Associated With Lipid Metabolism and Hosmentioning
confidence: 99%
“…It is proposed that glycolysis provides energy sufficient for the survival of schistosomes, while vitellocytes are highly dependent on oxidative phosphorylation of lipids [22]. Schistosomes infecting mice living on high-fat diets have a higher fecundity rate than worms infecting mice living with a regular diet [23]. Vitellogenesis was also enriched in the blue module.…”
Section: Expression Of Genes Associated With Lipid Metabolism and Hosmentioning
confidence: 99%
“…Analogies are evident in other parasite systems. For example, human daily ethanol ingestion has a positive association with frequency of Strongyloides stercoralis infection (Marques et al, 2010); chronic alcohol ingestion significantly reduces granuloma and hepatic fibrous tissue in mice infected with S. mansoni (Orrego et al, 1981; Castro et al, 1993); and a high-fat diet has a prominent effect on the course of chronic schistosomiasis mansoni in mice (Alencar et al, 2009). Modern molecular techniques are needed for better characterization of this phenomenon.…”
Section: Future Directionsmentioning
confidence: 99%
“…This suggests that infection influences the regulation of adiposity in obese mice. It has been shown that schistosomes are closely associated with lipid metabolism modulation (El Ridi et al 2004, Tallima & El Ridi 2005, Alencar et al 2009). IPR offspring presented only lower total fat when compared with non-IPR offspring.…”
Section: Table IVmentioning
confidence: 99%